Susceptibility to Metabolic Diseases in COVID-19: To be or Not to be an Issue - Kaviani, Maryam; Keshtkar, Somayeh; Soleimanian, Saeede; Sabet Sarvestani, Fatemeh; Azarpira, Negar; Pakbaz, Sara (Frontiers in Molecular Biosciences, 2022)
Despite the passage of more than 17 months from the beginning of the COVID-19 pandemic, challenges regarding the disease and its related complications still continue in recovered patients. Thus, various studies are underway to assay the long-term effects of COVID-19. Some patients, especially those with severe symptoms, experience susceptibility to a range of diseases and substantial organ dysfunction after recovery. Although COVID-19 primarily affects the lungs, multiple reports exist on the effect of this infection on the kidneys, cardiovascular system, and gastrointestinal tract. Studies have also indicated the increased risk of severe COVID-19 in patients with diabetes. On the other hand, COVID-19 may predispose patients to diabetes, as the most common metabolic disease. Recent studies have shown that Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) binds to Angiotensin-Converting Enzyme 2 (ACE2) receptors, which are expressed in the tissues and organs involved in regulating the metabolic status including pancreas, adipose tissue, gastrointestinal tract, and kidneys. Therefore, SARS-CoV-2 may result in metabolic disturbance. However, there are still many unknowns about SARS-CoV-2, which are required to be explored in basic studies. In this context, special attention to molecular pathways is warranted for understanding the pathogenesis of the disease and achieving therapeutic opportunities. Hence, the present review aimed to focus on the molecular mechanisms associated with the susceptibility to metabolic diseases amongst COVID-19 recovered patients.